Use of hCG for luteal support in natural frozen–thawed blastocyst transfer cycles: a cohort study - Wen, Wen; Li, Na; Shi, Juanzi; Zhou, Hanying; Fan, Lijuan (Frontiers in Endocrinology, 2024)
Introduction In the realm of natural frozen-thawed embryo transfer (FET) cycles, the application of luteal phase support (LPS) is a prevalent practice, primarily due to its beneficial impact on reproductive outcomes. Among the various LPS medications, human chorionic gonadotropin (hCG) is one that exerts its function on both the corpus luteum and the endometrium. Objective To evaluate the effect of hCG administration as LPS on reproductive outcomes in natural FET cycles. Methods This study was a retrospective cohort analysis conducted at a tertiary care hospital. It included women who underwent natural FET treatment from January 2018 to December 2022. Participants were divided into the hCG LPS group and the non-hCG LPS group on the basis of whether they used hCG as LPS after blastocyst transfer. The primary outcome was the clinical pregnancy and live birth rates. The secondary outcomes included the early miscarriage rate (before 12th gestational week) and total miscarriage rate. Results A total of 4762 women were included in the analysis, and 1910 received hCG LPS and 2852 received no hCG LPS (control group). In the general cohort, the clinical pregnancy and live birth rates in the hCG LPS group were significantly lower than those in the control group (63.82% vs 66.41%, aOR 0.872, 95% CI 0.765–0.996, P=0.046; 53.98% vs 57.15%, aOR 0.873, 95% CI 0.766–0.991, P=0.035, respectively). The early miscarriage and total miscarriage rates were similar between the two groups. In a subgroup analysis, in women who received an hCG trigger, there was no significant difference in the clinical pregnancy rate or live birth rate between the two groups. However, in women who ovulated spontaneously, the clinical pregnancy and live birth rates in the hCG LPS group were significantly lower than those in the control group (60.99% vs 67.21%, aOR 0.786, 95% CI 0.652–0.946, P=0.011; 50.56% vs 57.63%, aOR 0.743, 95% CI 0.619–0.878, P=0.001, respectively). Conclusion Among women undergoing natural cycle frozen–thawed blastocyst transfer, hCG LPS is associated with lower clinical pregnancy and live birth rates. Additionally, the adverse effect of hCG LPS is more pronounced in women who ovulate spontaneously.